Bekenilui pada Masyarakat Adat Lampung Pepadun Perspektif Hukum Islam dan Teori Konflik - Eka Oktaria Pratiwi (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Before the wedding in Mataram Marga Village, Sukadana District, East Lampung Regency, there is a tradition that is stiil valid today, namely the tradition of giving bekenilui money at the wedding. The fact is that in Mataram Marga Village, someone who wants to get married, at least a week before the wedding ceremoney, the prospective bridegroom must give a certain amount of money to the prospective brid’s family. There is no clear and difinite source for when tradition began to be implemented, but people have carried out this tradition from the past until now. The first aim of this reserch is why do the people of Mataram Marga Village, Sukadana District, East Lampung Regency have a tradition of using money in marriage? Second, how is the conflict between the people of Mataram Marga Village, Sukadana District, East Lampung Regency, due to the money tradition seen from Rafl Dahrendorf’s conflict theory? This reserch uses an empricl qualitative approach. Data collection by means of observation, interviews and docomentation. The analysis technique is carried out by data ruduction, data verification and data analysis, white checking the validity of the data is carried out using the triangulation method. The result of this research are (1) provision of cash in cash Marriages that take place in Mataram Marga Village are mandatory. If the propective groom does not comply, it can hinder his marriage, because according to society, this provision has become a tradition that has been in effect for generation from ancient times until now. However, along with the changes that occur in the social life of the community, (2) the opposition of the peopele of Mataram Marga Village to the tradition of giving this kind of money shows the truth of the essence of Rafl Dahrendrof’s conflicts over traditional money traditions in marriage are caused by pressure on the tradisional head as the supereordinate authority in datermining traditional money traditions. With the prospective groom as a subordinate who is required to provide money related to the marriage. The commonity involed in this conflict is divided into two groups, nemely, the traditional head and the bride’s family as a pseudo group, then the community, especially the prospective groom as an interest group.